PENGEMBANGAN SISTEM INFORMASI E-ARSIP SURAT MASUK DAN KELUAR (PT. SUMBER KALIMANTAN ABADI – SIDOARJO) - Putri Sa’adah, Maulidiana; Zulkarnain, Adnan; Resmiatini, Erna (Universitas Islam Balitar, 2024)
Sumber Kalimantan Abadi Sidoarjo has many administrative documents, including incoming and outgoing letters. However, the manual archiving process currently in use is prone to loss, duplication, or unconfirmation. To address this issue, the company has developed an e-archive system that is easily accessible and helps the document archiving process in a structured and detailed manner. The creation of this system involved field data collection, problem analysis, database design and system design, as well as system testing. Available features in this system include uploading physical evidence for incoming mail data, statistics, and notifications for confirmation. This system is designed to facilitate the archiving process and be accessed by company employees. The results of this study include systems that can replace manual filing with a computerized system, manage mail numbers automatically, manage notifications as confirmation of approval, manage incoming and outgoing mail of various types, and facilitate the process of printing outgoing letters in the form of softfiles or hardfiles.